PERAN PEMBELAJARAN SEBAYA DALAM MATEMATIKA: SEBUAH STUDI TENTANG MODEL PEMBELAJARAN KOOPERATIF TSTS - Yuwono, Timbul; Meriana Rita , Maria (Nabla Dewantara: Jurnal Pendidikan Matematika, 2025)
This study investigates the impact of the Two Stay Two Stray (TSTS) cooperative learning model on enhancing student achievement and engagement in mathematics education at SMPN 5 Welak, Manggarai Barat, Nusa Tenggara Timur. The research employs a Classroom Action Research (CAR) design, comprising two cycles of implementation. Cycle 1 revealed that 62.69% of students met the minimum competency level, while Cycle 2 demonstrated a significant improvement, with 82.76% achieving the target. Observational data indicated increased student participation and enthusiasm during group discussions, suggesting enhanced engagement. The peer exchange component of the TSTS model facilitated knowledge transfer and reinforced mathematical communication skills. However, challenges persisted for some students in independent problem-solving tasks, indicating the need for additional scaffolding. The findings underscore the effectiveness of the TSTS model in fostering collaborative learning environments that promote academic achievement and active participation. This research contributes to the body of knowledge on cooperative learning strategies in mathematics education and offers insights for educators seeking to implement interactive teaching methods. Future studies could explore the long-term effects of TSTS on student learning outcomes and its applicability across diverse educational settings